PENINGKATAN HASIL BELAJAR PPKN MATERI ANALISIS PENERAPAN NILAI-NILAI PANCASILA MELALUI MODEL BLENDED LEARNING BERBANTUAN MEDIA WHATSAPP - Rumini Rumini (JANACITTA, 2021)
The purpose of classroom action research is to determine the improvement of Civics learning outcomes for class VI C SDN Candi 01 Semarang City through the application of Blended Learning model assisted by WhatsApp media. Blended Learning combines the best of online learning, structured face-to-face activity, and real-world practice. WhatsApp is an internet-based application that makes it easy for users to communicate with the available features and the most popular social media. Based on the results of research and data analysis, it can be concluded that Whatsapp media can improve PPKN learning outcomes for analyzing the application of Pancasila values in class VI C SDN Candi 01 academic year 2020/2021.